Penguatan Kelembagaan Desa: Optimalisasi Kelembagaan Desa Budaya Wirokerten melalui Legalitas dan Branding - Putri, Nazwa Amalia; Asfahanny, Salwa Keinda; Tyas, Dian Restuning; Tsabita, Aida Fathya; Abdurrahman, Abdi; Elantri, Aulia Rahmawati; Akbar, Muhammad Bintang; Sakir, Sakir (Universitas Muhammadiyah Yogyakarta, 2025)
This article aims to describe the institutional strengthening of Wirokerten Cultural Pilot Village through supervision of the establishment of identity and legality, as well as the branding of Cultural Pilot Village arts. This program was implemented in three main stages, namely problem identification, program conceptualization, and program implementation. Based on the results of the identification, three main problems were found: first, the absence of legality or legal umbrella, such as the making of the legality of the Arts Identification Number (NIK); second, the absence of a clear identity in each art of Wirokerten Village; third, the absence of art branding causes a lack of massive promotion of art in Wirokerten Village. From the data collection results, it is known that problems related to culture are the most dominant, with a percentage reaching 62% of Wirokerten people not knowing the exact number of regional arts. The service method used is the community assistance method. At the conceptualization stage, the proposed program includes supervision of making the legality of the Arts Identification Number (NIK) and promoting the culture of Wirokerten Village. The supervision was carried out by involving eight heads of hamlets in Wirokerten Village. The main objective of this supervision is to ensure that every art form in Wirokerten Kalurahan has a legality letter that serves to protect local culture and gain official recognition. In addition, this program aims to create a clear and distinctive identity for village culture, optimize promotion through social media, and increase the institutional capacity of village officials. The results of the program show that institutional strengthening through legality and art branding can increase public awareness of the importance of cultural preservation. This is evidenced by the registration of 33 arts whose legality has been submitted to the Auxiliary Culture Office and the Instagram account @desabudaya.wirokerten as a forum for branding Wirokerten village arts. This success can be the basis for further service with a focus on integrating the Wirokerten Village Cultural Pilot in the context of broader and sustainable cultural development. Thus, the strengthening of culture-based village institutions is expected to become a model for the development of other villages that have similar potential